Pengaruh Waktu Blanching Terhadap Karakteristik Tepung Kernel Biji Mangga Arumanis (Mangifera indica L.) - Utami, Ni Kadek Ayu Nira; Wiadnyani, Anak Agung Istri Sri; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
The significant sources of horticultural waste in Indonesia is mango seed waste. The high starch content in mango seeds allows for their conversion into flour. A common issue in processing mango seed kernel flour is the propensity for browning. Therefore, blanching is necessary to improve the physicochemical characteristics of the mango seed kernel flour. The aim of this study is to determine the effect of blanching time on the characteristics of the flour and to identify the optimal blanching duration to produce mango seed kernel flour with the best characteristics. This research was conducted using a Completely Randomized Design (CRD) with 5 levels of blanching times treatments: P0 (0 minutes), P1 (5 minutes), P2 (10 minutes), P3 (15 minutes) dan P4 (20 minutes), each replicated three times for a total of 15 experimental units. The data collected were analyzed using analysis of variance, and if there was a significant treatment effect on the observed parameters, further testing was conducted using the Duncan Multiple Range Test (DMRT). The results showed that blanching time significantly (P<0.05) affected moisture content, starch content, total phenols, pH, and color. The 15-minutes blanching treatment produced the best characteristics in the Arumanis mango seed kernel flour, with 6,40% moisture, 50,45% starch, 17,41 mg/g total phenols, 0,91% ash content, 12,87% fat content, 7,36% protein content, 72,45% carbohydrate content, 9,90% crude fiber, 31% yield, a pH of 6,31, and the color with L* value of 84.3, a* value of 1,7 and b* value of 5,0 . Keywords: flour, mango seed, blanching times